Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]\frac{x^2+6x+5}{x^2-25}=(*);\ x^2-25\neq0\to x^2\neq25\to x\neq-5\ \wedge\ x\neq5\\\\x^2+6x+5=0\\\\\Delta=6^2-4\cdot1\cdot5=36-20=16;\ \sqrt\Delta=\sqrt{16}=4\\\\x_1=\frac{-6-4}{2\cdot1}=\frac{-10}{2}=-5;\ x_2=\frac{-6+4}{2\cdot1}=\frac{-2}{2}=-1\\\\x^2+6x+5=(x+5)(x+1)[/tex]
[tex](*)=\frac{(x+5)(x+1)}{(x-5)(x+5)}=\frac{x+1}{x-5}[/tex]
[tex](*)=\frac{(x+5)(x+1)}{(x-5)(x+5)}=\frac{x+1}{x-5}[/tex]
[tex] \frac{x^2+6x+5}{x^2-25}= \frac{x^2+6x+5}{(x-5)(x+5)}=(*) \ \ \\ \\.\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x -5\neq 0\ \ and\ \ x+5 \neq 0\ \ \Rightarrow\ \ x\in R\setminus \{5;-5\}\\ \\x^2+6x+5=(x+5)(x+1)\\ \\because:\\\Delta=6^2-4\cdot1\cdot5=36-20=16\ \ \Rightarrow\ \ \sqrt{\Delta} = \sqrt{16} =4\\ \\ x_1= \frac{-6-4}{2\cdot1} = \frac{-10}{2} =-5,\ \ x_2= \frac{-6+4}{2\cdot1} = \frac{-2}{2} =-1\\ \\ \\ (*)= \frac{(x+5)(x+1)}{(x-5)(x+5)} = \frac{x+1}{x-5} [/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.